General Physical Preparation of Freestyle Wrestlers: An Advanced Approach - Nodir Khanturaev (International Journal on Integrated Education, 2023)
Abstract: The attainment of superior athletic outcomes in Freestyle wrestling hinges significantly upon the elevated physical conditioning of the wrestler, coupled with the refinement of key physical attributes such as flexibility, speed, strength, agility, and endurance. Consequently, the intricately intertwined processes of honing wrestling techniques and advancing physical preparedness assume pivotal roles in the realm of Freestyle wrestling. The absence of proficient technique not only exposes athletes to the risk of injury but also necessitates expeditious rectification to ensure the athlete's readiness for both training and competitive endeavors. Moreover, a critical facet involves a meticulous evaluation of the requisite levels of physical fitness tailored to the demands of the training regimen and competitive landscape. Wrestlers must attune their physical prowess, encompassing both health-related and skill-specific components, to the exacting standards mandated by Freestyle wrestling and its performance metrics. This article elucidates the array of exercises strategically employed to elevate the physical preparedness of Freestyle wrestlers, focusing on both general and targeted facets of physical conditioning.